Invitation to public speaking - Griffin, Cindy L. (Wadsworth series in speech communication, 2009)
Aims to provide you with public speaking skills that will serve you well in the classroom and beyond. This text shows you the power and importance of public speaking in your life, as well as in the community. It includes speech-building help and real-life examples in every chapter that help you understand the basic concepts